Exploring the implementation of poslansia, Indonesia's community‐based health programme for older people. (20th May 2016) - Christiani, Yodi; Byles, Julie E; Tavener, Meredith; Dugdale, Paul
Abstract : Aim: To explore the implementation of poslansia, a community‐based integrated health service implemented across Indonesia to improve the health status of older people through health promotion and disease prevention. Methods: Data analysis of 307 poslansia surveyed in the 4th wave of Indonesia Family Life Survey (IFLS‐4). We examined the services provided in the programme, resources and perceived problems. Results: The services provided by poslansia focused mostly on risk factor screening and treatment for minor illness, and less on health promotion activities. Lack of support from community health centres, no permanent place for holding poslansia and lack of participant interest in joining the programme were associated with fewer services provided in the programme ( P < 0.05). Conclusion: The findings indicate existing support from the community, community health centres and related institutions for poslansia is not adequate for optimal service function. Health awareness among the older population should also be increased for programme sustainability.